Agile-Based Field Internship Information System for Academic Administration Digitalization - Made Pradnyana Ambara; I Made Agus Oka Gunawan; I Wayan Rizky Wijaya (Jurnal Teknologi Informasi dan Pendidikan, 2026)
This study presents the development of a web-based internship management information system (PKL) aimed at improving the efficiency, transparency, and accountability of internship administration and supervision processes in the Department of Information Technology, Politeknik Negeri Bali. The system was developed using the Agile methodology to allow iterative and adaptive development, supported by the CodeIgniter 4 framework for lightweight and modular implementation. Core system features include online registration, internship letter submission, document uploads, supervision logs, and lecturer monitoring tools, all integrated to facilitate collaboration among students, supervisors, and administrators. The system’s performance was evaluated using black-box testing, which confirmed valid results across all major functional requirements, ensuring technical reliability. Furthermore, a usability assessment using the System Usability Scale (SUS) involving 20 respondents produced a score of 84.50, categorized as excellent, indicating high user satisfaction, ease of use, and efficiency. These findings demonstrate that the system not only fulfills its functional objectives but also enhances the digital transformation of vocational academic services, offering a replicable and scalable model for other educational institutions aiming to modernize their internship management processes.